Branco/a demais para ser negro/a e negro/a demais para ser branco/a: processos de racialização de juventudes que se reconhecem como pardas e periferizadas em Fortaleza (CE) - Cardoso, Rita de Cássia da Silva (2025)
This research investigated the processes of racialization of young people living in the outskirts of Fortaleza who self-identify as mixed-race. The guiding question of the research was: How does the process of racialization occur among young people living in the outskirts of the capital of Ceará who self-identify as mixed-race? The general objective was to analyze how the process of racialization unfolds among young people living in the outskirts of the capital of Ceará who self-identify as mixed-race. The specific objectives were: 1) To understand the narratives and meanings about being mixed-race that young people who self-recognize as such produce in their life trajectories and experiences, considering the intersectionality of race, gender, and class; 2) To discuss the role of interracial family relationships in the process of racialization of young people who recognize themselves as mixed-race; and 3) To reflect on the psychosocial effects that being recognized as mixed-race produces and the experiences of transformation of this racialization process in the life trajectories of young people in peripheral urban contexts. The research was conducted through a qualitative, inter(in)ventive, and participatory approach, grounded in a decolonial perspective and in the concept of "escrevivência" (writing-living), developed by Conceição Evaristo, as a methodological and political strategy. It was carried out with young students from a high school in Grande Bom Jardim and operationalized through two methodological devices: 1) workshops on racialization processes; 2) autobiographical interviews. The analysis of the narratives was guided by the episodic approach proposed by Kilomba (2019), valuing the meanings constructed by the embodied experiences of the participants and drawing on theoretical contributions from authors such as Frantz Fanon (sociogenesis and the psychosocial effects of racism), Achille Mbembe (coloniality and necropolitics), Lélia Gonzalez, Sueli Carneiro, and Cida Bento (race, whiteness, and Black subjectivity), Carla Akotirene (intersectionality), Neusa Santos Souza (Black identity and subjectivity), among others. This research affirms "escrevivência" (Evaristo, 2017) as an ethical and political force in denouncing racial violence and asserting other possibilities of existence for mixed-race youth from peripheral communities. The results reveal that being recognized as mixed-race is experienced as a racial identity limbo, marked by ambiguities, silences, and conflicts in family and school relationships. The narratives indicate that racial self-recognition as Black emerges from experiences of pain, exclusion, and violence, but also from collective encounters that enable racial literacy and the construction of positive meanings about Blackness. The research highlighted that the process of racialization intersects with markers of class, gender, and generation, producing psychosocial effects that encompass issues such as self-hate, but also experiences of belonging and re-existence.